Meningkatkan Aktivitas Belajar Dan Keterampilan Berpikir Kritis Muatan IPS Menggunakan Model Pintar Pada Kelas IV Di SDN Beringin 2 - Assa’adah Napisah; Akhmad Riandy Agusta (CV. ITTC INDONESIA, 2024)
The problem in this study is that students are still passive in participating in learning and critical thinking skills in social studies content. This is due to the lack of student interest in social studies content regarding the condition of the surrounding area plus learning that is delivered using conventional methods so that students feel bored and get bored quickly. The purpose of this study was to describe teacher activities, describe student activities, analyze the effect of the PINTAR model on students' critical thinking skills, and analyze the effect of the PINTAR model on student learning outcomes. This study used Classroom Action Research (PTK) which was carried out in 3 meetings. The subjects of this study were fourth grade students at SDN Beringin 2, with a total of 25 students consisting of 14 male students and 11 female students, in semester II of the 2022/2023 academic year. The results of this study showed an increase in the quality of teacher activity at meeting III obtained a score of 51. Student activity at meeting III obtained an increase of 88%. The critical thinking skills gain 84%. Meanwhile, for classical completeness, student learning outcomes at meeting III obtained a percentage of 88%.